(untitled) (Universal International Scientific Journal, 2026)
In this article, we will witness how the concept of Arifism presented in Alisher Navoi’s work "Nasayimul Muhabbat" is interpreted. It will also analyze how the Sufis mentioned in the work expressed their views and interpretations of Arifism. It will also examine Arifs and their types, the classes and categories of saints according to Alisher Navoi’s interpretation, and their unique aspects.